Transbronchial lung biopsy for the diagnosis of IgG4‐related lung disease. Issue 1 (2nd May 2018) - Otani, Kyoko; Inoue, Dai; Itoh, Tomoo; Zen, Yoh
Abstract : Aims: The diagnosis of IgG4‐related disease (IgG4‐RD) requires a multidisciplinary approach, in which histology plays an important role. Although a diagnosis was previously established by the use of surgically resected specimens, there is increasing clinical demand to diagnose this systemic condition by the use of biopsies. The aim of the present study was to elucidate how useful transbronchial lung biopsies (TBLBs) are for this diagnostic purpose. Methods and results: The study cohort consisted of 20 consecutive patients diagnosed with IgG4‐RD in other organs who underwent TBLB for potential pulmonary involvement. One case showing multiple granulomas suggestive of other conditions was excluded. Seven of the remaining 19 cases (37%) showed apparently normal lung tissue, indicating a sampling error, and 12 (63%) had microscopic abnormalities. Nine cases (47%) with a dense lymphoplasmacytic infiltrate met the number and ratio criteria for IgG4‐positive plasma cell infiltration (>20 cells/high‐power field, and an IgG4/IgG‐positive plasma cell ratio of >40%). Obliterative phlebitis and storiform fibrosis were observed in one case each. In 43 control cases of various inflammatory conditions, tissue IgG4 elevations appeared to be uncommon, with only two cases (5%) each meeting the number or ratio criterion, and one case (2%) fulfilling both. All control cases with tissue IgG4 elevations were of eosinophilic pneumonia. Conclusions: Transbronchial lung biopsies provided histological findings that were supportive for the diagnosis of IgG4‐RD in 47% of cases, with 98% diagnostic specificity. Therefore, they have potential as a useful and acceptable diagnostic approach for IgG4‐related lung disease.